A presença das ideias da Escola Tropicalista Baiana nas teses doutorais da Faculdade de Medicina (1850-1889) - Santos, Adailton Ferreira dos (2012)
We point out in this research the Doctoral Theses of the Bahia Medicine College in the second half of the nineteenth century, period of a controversial context, of the development of the country and also of the diseases that caused the death of many workers and slaves. In the medical sciences predominated miasmatic theories and practices like the quarantine and the kidnapping to combat the epidemics. Due to this situation arises the discussions and the debates in the scientific scenery and also the education reforms that, in turn, allowed changes in the Medicine College. So arise other medical practices and also the original works of the Bahia Medical Tropicalist School, which they were dedicated to assisting to the poorest and they study tropical diseases founded on the parasitic theories. Therefore, the investigation of the Doctoral Theses told us that the Bahia Medicine College, from the 70s adopts ideas and the original works of the Bahiana Tropicalist School for medical education and this modifies its trajectory in Brazil